PENGARUH PUPUK FOSFOR DAN GIBERELIN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum melongena L.). - Ayu Robby; Nurbaiti Nurbaiti; Murniati Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research aims to find out the effect of phosphorus fertilizer doses at various concentrations of gibberellins, gibberellin concentration on various doses of phosphorus, the main effects of phosphorus fertilizer and gibberellin which is better for growth and the yield of eggplant plants. The research was conducted at the UPT of the Faculty of Agriculture Universitas RiauPekanbaru starting from January to April 2018 was experimentally arranged in divided plot design using arandomized block design. The main plot is the gibberellin concentration (0, 5, 10 and 15) ppm. The sub plot is the dose of phosphorus fertilizer (92, 138 and 184)kg of P2O5ha-1. The parameters observed: plant height, days to flowering, amount of flowers per plant, harvesting day, amount of fruits per plant, fruit length, fruit diameter and fruit weight per plant. The combinationtreatment phosphorus 184 kg P2O5.ha-1 and giberellin of 15 ppm is better on plant height, days to flowering, amount of flowers and harvesting age. The treatment 92 kg of P2O5.ha-1 and without being given giberellin can increasebetter on the amountof fruits and fruit weight. The treatmentphosphorus at the dose of 92 kg P2O5ha-1 produced the better amount of fruits and fruit weights. The treatment of without gibberellin increased the amount of fruits and the better fruit weight until 90 days of planting. Key words: eggplant plant, phosphorus fertilizer and gibberellins.